The Prospects of Using Biogas: Technological Achievements, Ecological and Economic Efficiency, Development in Global Energy - Akhmetov, Nurlan; Yuldashbek, Davlat (International Journal of Environmental Science and Green Technology, ISSN: 3080-8693, 2025)
This article examines various aspects related to biogas production, its technological features, economic advantages, and the challenges faced by the industry. Biogas, as an important renewable energy source, is a mixture of methane (CH4) and carbon dioxide (CO2) that forms during the anaerobic decomposition of organic materials. With the increasing environmental and economic issues associated with the use of fossil fuels, biogas has become a promising solution for reducing carbon emissions and recycling waste. The article analyzes global trends, current statistical data, and prognostic conclusions about the development of the biogas sector in the coming decades. It also focuses on the current state of biogas production in the world and Kazakhstan, as well as the potential for expanding this sector in the context of sustainable development.